The Leadership Molecule Hypothesis: Implications for Entrepreneurial Organizations - Flamholtz, Eric G. (Senate Hall, 2011)
The topic of leadership in entrepreneurial organizations has received relatively little attention. The prevailing view is that leadership is an individual phenomenon. This paper proposes that the conventional notion of a "single heroic leader" in companies is an inadequate explanation how leadership actually works in entrepreneurial organizations as they evolve over time. Although it might appear that there is a single charismatic leader who determines the success of a company; if we look more closely there is typically a "core leadership team" (in the true sociological sense) with defined but overlapping and complementary roles. Specifically, this team is actually performing five key "strategic leadership functions" (defined below) as a collective unit rather than as a set of individuals. This team of leaders has been termed "the Leadership Molecule" (Flamholtz and Randle,2008). This article addresses some key issues concerning leadership in entrepreneurial businesses: What are the core tasks of leadership in rapidly growing entrepreneurial businesses? Do leadership requirements change as a company grows and develops? If requirements do change, then how does leadership need to evolve at different stages of entrepreneurial growth? Can leadership in entrepreneurial firms continue to be exercised by a single individual as a company grows, or if not then what "form of leadership" is required? It also provides some empirical support for the proposed construct of the leadership molecule based on a study of entrepreneurial leaders in China. Keywords: Leadership, Entrepreneurial Leadership, Leadership Functions, Strategic Leadership, Leadership Molecule.
Keywords: leadership|entrepreneurial leadership|leadership functions|strategic leadership|Leadership Molecule